ISSUES OF INTOLERANCE AND RADICALISM IN THE ANIMATION "NUSSA OFFICIAL - Fika Rizky Auliya; Sumardjijati (JOSAR (Journal of Students Academic Research), 2022)
YouTube media is a media used by people of all ages, including children. Animation has become one of the most common shows watched by children. However, the show "Nussa Official" from the Youtube platform was accused of having issues of intolerance and radicalism. This study uses a qualitative approach with the method of reception analysis Stuart Hall, which categorizes into three types of acceptance .. The results show that public acceptance in accepting the issue of intolerance and radicalism have their respective perceptions. In accepting the issue of intolerance, none of the informants occupy a dominant hegemonic position, while in the case of radicalism, the informants are in all positions, namely dominant-hegemonic code, negotiated code and oppositional code.